3 Kg LPG Business Strategy Development Using BMC and BOS - Hanifianto, Luqman; Noer, Bustanul Arifin (Institut Teknologi Sepuluh Nopember, 2020)
Arief LPG is a new distributor that distributes 3 kg LPG gas in the Menanggal area, Surabaya. As a new distributor Arief LPG will face existing competitors, be able compete Arief LPG must have a business model that can be used as a reference for the business being undertaken. Tools that can be used to analyze business models are using Business Model Canvas (BMC) and Blue Ocean Strategy. Using Business Model Canvas and Blue Ocean Strategy can be used to create a new business model design. This study aims to map, evaluate and improve Arief LPG's business model. The method used in this study is by interviewing Arief LPG customers. Results obtained from the Business Model Canvas are adding types of LPG that are sold LPG 12 Kg in addition promotions that can be done using online media such as creating a personal Blog or Web, and other social media. While results of the Blue Ocean Strategy factors that need be reduced accuracy of delivery, factor that needs improved is increase the amount of 3 kg LPG distribution, and create factors that have never been sold, such Bright Gas, 12 kg LPG and making a training on gas handling.